Development and validation of the Ibadan Simplified Developmental Screening chart - Lagunju, I. A.; Adeniyi, Y.; Orimadegun, A. E.; Fernandez-Reyes, D. (Frontiers in Pediatrics, 2023)
Background Developmental assessment remains an integral part of the routine evaluation of the wellbeing of every child. Children in resource-poor countries are not routinely assessed for signs of developmental delay and developmental disorders are frequently overlooked. A major gap exists in the availability of culturally appropriate and cost-effective developmental screening tools in many low and middle income countries (LMICs) with large populations. Objective To bridge the existing gap, we describe the process of the development and validation of the Ibadan Simplified Developmental Screening (ISDS) chart, for routine developmental screening in Nigerian children. Methods We developed an item pool across 4 domains of development namely, the gross motor, vision-fine motor, communication and socio-behavioural domains. The ISDS chart consists of 3–4 item questions for each domain of development, and responses are to be provided by the caregiver. Each chart is age-specific, from 6 weeks to 12 months. A total score derived from the summation of the scores in each domain are plotted on the ISDS scoring guide with a pass or fail score. Each child was evaluated by the Ages and Stages Questionnaire as the standard. Results A total of 950 infants; 453 males and 497 females were enrolled. The estimates of internal consistency between the two instruments ranged between 0.7–1.0. Using the ASQ as the gold standard, the ISDS chart demonstrated a sensitivity of 98.8%, 78.4% and 99.7% in the gross motor, communication and the social and emotional domains respectively, for detecting infants who might require further assessment for developmental delays. Conclusion The indigenous tool fills a major gap in the need for cost-effective interventions for developmental monitoring in LMICs. Future work should include the deployment of the tool in the wider population, using digital health approaches that could underpin policy making in the region.